Peningkatan Produktivitas Pulp dan Kertas dengan Pendekatan Green Productivity PT. Riau Andalan Pulp And PaperKabupatenPelalawan - Fakhruni Alisya; Farida Hanum Hamzah; Yelmira Zalfiatri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
The increase of consumer demand for pulp and paper encourage PT. Riau Andalan Pulp and Paper to be able to improve its production and performance in order to compete with other similar companies. However, along with the enhancement in production, it also increase the amount of waste generated. The increasing amount of waste due to the increased of production capacity encourages PT. Riau Andalan Pulp and Paper to minimize production waste by using a method called green productivity in order to improve the environmental performance. Based onresearch done in PT. Riau Andalan Pulp and Paper, there are two alternative solutions to minimize waste that also improve the productivity and environmental performance which was to burn the sludge produced from IPAL and to produce fertilizer from IPAL sludge. However, the green productivity index of the first alternativewas biggerthan the second alternative which is 3,98. The chosen alternative was toburn the sludge produced from IPAL to the power boiler. This solution increased productivity, where the initialproductivity was2,31 to 2,43. The chosen alternative solutions may improve the environmentalperformance indicator from 0,59to0,61.Keywords:   green productivity, productivity, environmental performance indicator, PT. Riau Andalan Pulp and Paper